Cyto-histological correlation in diagnosis of gastrointestinal lesions- a prospective study in a tertiary care institute - Aggarwal, Swati; Mardi, Kavita; Sood, Shivani; Kaushal, Vijay; Sharma, Brij; Sood, Pranav (International Journal of Research in Medical Sciences, 2020)
Background: Gastrointestinal tract is involved by a large number of inflammatory, infectious and neoplastic diseases. There is a worldwide rising incidence of GIT lesions especially neoplasms. Methods: This study was planned to correlate endoscopic and colonoscopic brush cytology with histopathology of gastrointestinal lesions and to determine the spectrum of gastrointestinal lesions in patients subjected to endoscopic brushings and biopsy. Results: Sensitivity of upper GI brush cytology was 95.15% and specificity 90.41%. Sensitivity of colonoscopic brush cytology was 100% and specificity 86.79%. The accuracy of brush cytology came out to be 92.45% in upper GIT and 92.22% in lower GIT. Conclusions: Brush cytology is a non-invasive and cost-effective method to retrieve epithelial cells from a much larger surface area of the mucosa, thus allowing thorough sampling and increasing the diagnostic yield.